On the Calculation of Implied Volatility Using A Genetic Algorithm - Kuntjoro Adji Sidarto (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2006)
In the Black-Scholes options pricing formulas one parameter that cannot be directly observed is the volatility of the stock price. If actual market data of the price V are known, then the volatility can be viewed as unknown and can be calculated via the implicit equation (),,,,,0VvSTtKrσ−=.The volatility σplays the role of the unknown parameter. The volatility σdetermined in this way is called implied volatility and is the root of the equation()(),,,,,0fVvSTtKrσ σ =− = . Iterative methods such as Newton’s method, can then be used to find the root. In this work we propose an approach that uses a genetic algorithm to find the implied volatility.Keywords: option pricing, implied volatility, genetic algorithm